Efficient Market Adjustment of Odds Prices to Reflect Track Biases - Canfield, Brian R.; Fauman, Bruce C.; Ziemba, William T. (Management Science, 1987)
Biases that reflect the economic worth of uncertain contingent claims occur in many financial markets. Parimutuel betting at racetracks is one such market with ample data to investigate such biases. The total wagering market is about $10 billion per year in North America. The configuration of racetracks leads to an advantage for horses breaking from post positions near the rail, especially for tracks with small circumferences. Can the bettor make profits with knowledge of this bias? To investigate, we utilize data from 3,345 races involving over $300 million in wagers from 1982, 1983 and 1984 on win and exotic bets at Exhibition Park in Vancouver where this bias should be strong. The results indicate that the bias exists but the prices adjust to fully negate the potential gains from the bias.